Pariwisata Sebagai Media Komunikasi Budaya Berkelanjutan (Studi Deskriptif Kualitatif di Kabupaten Lombok Utara) - I Putu Gede; Syech Idrus (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2020)
Tourism as a medium of communication, strengthens cultural values ​​in terms of the tourist attraction of a region. Cultural values, can provide benefits to social, environmental and economic aspects. This study used an exploration approach, the data was collected using in-depth interviews, observation, and literature review. The results of this study prove that tourism can be a medium of communication in strengthening the development of sustainable cultural values, if communicated well and effectively by interested parties namely, government, businessmen, the community including Sasak Customary Institutions and other groups, such as Tourism Awareness Group, it can be presented the integrity of the display of art based on local wisdom which is supported by the beauty of the panorama of nature, so as to strengthen and increase the popularity of a Tourist Attraction.